Établir le texte de Trois contes - Stéphanie Dord-Crouslé (Flaubert: Revue Critique et Génétique)
As Three Tales is published in the fifth volume of Flaubert’s Complete Works (“Bibliothèque de la Pléiade”, May 2021), this article is interested in the complex problems raised by its establishment: the history of this special text is first accurately related using all available external sources; the question of the enigmatic “Laporte manuscript” is then examined; finally, the principles that guided the establishment of the text for the new edition are set out.